NATIVE-ACCENT LISTENING MATERIALS SEBAGAI SUMBER OTENTIK DALAM PENGEMBANGAN BAHAN AJAR GENERAL ENGLISH - Yuniarti Yuniarti (FKIP UM Pontianak, 2021)
ABSTRACT Teaching materials play an important role in the teaching and learning process both for lecturers students. This study aimed at developing General English teaching materials based on native-accent listening materials as an authentic source for students of Universitas Muhammadiyah Pontianak. The method used in this research was the ADDIE development model by Dick, Carey and Carey (2009); analysis, design, development, implementation and evaluation. Data of this study were collected using questionnaires and interview. A total of 30 students who were representatives of 12 study programs at UM Pontianak participated as respondents. The results show that students were more interested in native accent-listening materials sourced from You Tube because it was considered more up-to-date. Students also tend to choose material with easy to difficult level of to enhance their vocabulary mastery, short conversation of listening audio (video) completed with ‘glossary study’ in each chapter of the module. In addition, the use of listening material sources was preferred in a ready-to-use form without having to download them. Data from the analysis of student questionnaires on the needs of the General English module indicates that the majority of students were more interested in integrated skills materials (listening, speaking, reading, writing) completed with descriptions and learning objectives and time allocation of each chapter, contained topics that are in accordance with the available time, presented with various practice questions and glossary study activities, presented in legible fonts and relevant visuals or pictures. In short. The module is expected to facilitate students with effective, motivating, and practical materials.